1999
DOI: 10.1016/s0014-5793(99)00111-8
|View full text |Cite
|
Sign up to set email alerts
|

On the binding of ATP to the autophosphorylating protein, Ptk, of the bacterium Acinetobacter johnsonii

Abstract: The autophosphorylating protein, Ptk, of the bacterium Acinetobacter johnsonii was overproduced, purified to homogeneity and assayed for ATP binding by using the nucleotide analog 5P-p-fluorosulfonylbenzoyl adenosine. The ATP binding site of this bacterial autophosphorylating protein was found to be different from that generally used by eukaryotic protein kinases. It consists of two amino acid sequences that closely resemble the Walker motifs A and B. This observation was confirmed by site-directed mutagenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…4 pUC18-wzc K540M -rcsA ϩ , was prepared. This plasmid encoded a Wzc protein modified in the ATP-binding site, at the level of the lysine residue at position 540 that is essential for overall phosphorylation (11,40). E. coli JM83 wzc::Km R cells carrying this construct were subjected to 0.5% formaldehyde treatment, and then the protein content was analyzed by electrophoresis and immunoblotting with anti-Wzc.…”
Section: Fig 2 In Vivo Cross-linking Of Wzc In E Coli Cellsmentioning
confidence: 99%
“…4 pUC18-wzc K540M -rcsA ϩ , was prepared. This plasmid encoded a Wzc protein modified in the ATP-binding site, at the level of the lysine residue at position 540 that is essential for overall phosphorylation (11,40). E. coli JM83 wzc::Km R cells carrying this construct were subjected to 0.5% formaldehyde treatment, and then the protein content was analyzed by electrophoresis and immunoblotting with anti-Wzc.…”
Section: Fig 2 In Vivo Cross-linking Of Wzc In E Coli Cellsmentioning
confidence: 99%
“…1). PTKs of Gram-negative bacteria are usually large proteins (ϳ80 kDa) composed of an N-terminal transmembrane domain and a C-terminal cytosolic PTK domain (22) containing the active site Walker motifs A and B (23). When expressed separately, the soluble C-terminal domain of E. coli Wzc still exhibits autophosphorylating activity (24).…”
mentioning
confidence: 99%
“…These various proteins share several common structural features specific to bacteria, namely the Walker A and B ATPbinding motifs (17), which are not usually found in the counterpart eukaryotic kinases, and a series of tyrosine residues clustered at the C-terminal end of the molecule. For Ptk and Wzc, the Walker A motif has been shown to be effectively employed for autophosphorylation of the protein on tyrosine, suggesting that bacteria utilize for phosphorylation a novel mechanism different from that of eukaryotes (10,17).…”
mentioning
confidence: 99%
“…For Ptk and Wzc, the Walker A motif has been shown to be effectively employed for autophosphorylation of the protein on tyrosine, suggesting that bacteria utilize for phosphorylation a novel mechanism different from that of eukaryotes (10,17). On the other hand, it has been suggested that the tyrosine cluster would be the target sequence for autophosphorylation (10,18), but no accurate characterization of the concerned residues has been made and its function remains unknown.…”
mentioning
confidence: 99%